PENGARUH FAKTOR-FAKTOR KEPENDUDUKAN TERHADAP PERTUMBUHAN EKONOMI DI KOTA MEDAN - Lailan Safina Hasibuan (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2014)
This study analysis how the influence of population growth, labor and the dependency ratio on economic growth in Medan. The method used in this study is Ordinary Least Square (OLS). The data used are time series from2003 to 20011 Regression analysis showed that the population growth variable is negative and significant impact on economic growth in Medan. Labor variable has positive and significant impact on economic growth in Medan. While the variable dependency ratio is significant and negative impact on economic growth in Medan